The orchid throne - Kennedy, Jeffe, 1966- (St. Martin's Paperbacks, 2019)
As Queen of the island kingdom of Calanthe, Lia will do anything to keep her people free<U+2014>and her secrets safe<U+2014>from the mad tyrant who rules the mainland. Guided by a magic ring of her father<U+2019>s, Lia plays the political game with the cronies the emperor sends to her island. In her heart, she knows that it<U+2019>s up to her to save herself from her fate as the emperor<U+2019>s bride. But in her dreams, she sees a man, one with the power to build a better world<U+2014>a man whose spirit is as strong, and whose passion is as fierce as her own<U+2026> Conrí, former Crown Prince of Oriel, has built an army to overthrow the emperor. But he needs the fabled Abiding Ring to succeed. The ring that Lia holds so dear to her heart. When the two banished rulers meet face to face, neither can deny the flames of rebellion that flicker in their eyes<U+2014>nor the fires of desire that draw them together. But in this broken world of shattered kingdoms, can they ever really trust each other? Can their fiery alliance defeat the shadows of evil that threaten to engulf their hearts and souls?